Regional Financial Independence, Local Revenue Effectiveness, and Expenditure Ratios Influencing Human Development Index in Seluma Regency - Joki Andriano; Pakri Pakri; Fitriani Ariska (Jurnal Ekonomi Balance, 2026)
Human Development Index (HDI) is a key indicator of regional development performance because it reflects achievements in health, education, and living standards. Despite continuous fiscal decentralization reforms, Seluma Regency has consistently recorded the lowest HDI in Bengkulu Province, raising concerns regarding the effectiveness of regional fiscal management. This study examines the effects of the Regional Financial Independence Ratio, Local Own-Source Revenue (PAD) Effectiveness Ratio, and Regional Expenditure Ratio on the Human Development Index in Seluma Regency during 2013–2023. A quantitative explanatory approach was employed using secondary time-series data obtained from the Central Statistics Agency (BPS) and the Directorate General of Fiscal Balance (DJPK). Multiple linear regression analysis was conducted using EViews 12 after satisfying classical assumption tests. The findings indicate that the Regional Financial Independence Ratio has a positive but statistically insignificant effect on HDI. In contrast, the PAD Effectiveness Ratio demonstrates a significant negative effect, suggesting that improved revenue realization does not necessarily translate into better human development outcomes when expenditure allocation remains inefficient. Furthermore, the Regional Expenditure Ratio exhibits a positive but insignificant relationship with HDI. Simultaneously, all independent variables significantly influence HDI, indicating that regional fiscal performance collectively contributes to human development. These findings emphasize that strengthening fiscal capacity alone is insufficient without improving the quality and effectiveness of public expenditure allocation. The study contributes to the fiscal decentralization literature by providing empirical evidence from a relatively underexplored Indonesian regency and offers policy recommendations for enhancing human development through more strategic, accountable, and outcome-oriented regional fiscal management.